5G Technology Transformation In Tourism - Pradini, Gagih; Awaloedin, Dipa Teruna; Agustiani, Fitri; Kelly, Ahmad (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2024)
The transformation of 5G technology has significantly impacted various aspects, including the tourism industry. With much higher speed and capacity than previous technologies, 5G enables the creation of more immersive and connected tourism experiences. Purpose This study explores the impact of implementing 5G technology on the tourist experience in certain destinations. Specific objectives include: Explain changes in the traveller experience following the implementation of 5G technology. Identify factors influencing traveller perception and satisfaction related to applying 5G technology. Analyse the challenges and opportunities of adopting 5G technology in the tourism sector. This research method uses a descriptive qualitative approach and SWOT analysis.